Hidrolisis Limbah Tongkol Jagung Menggunakan Asam Sulfat Dengan Variasi Waktu Fermentasi - Ellysa Loviani; Nani Sofroh; Wahyu Firmansyah; Andri Kapuji (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
the Indonesian people and the world in general. This problem has triggered exploration of alternative materials that can be used as substitute fuels for fuel oil. Corn cobs are one of the alternative ingredients that can be converted into liquid fuels. Corn cobs which are hydrolyzed to produce glucose are then fermented to produce ethanol. This research carried out the hydrolysis step against corncob to become glucose so that it can be fermented into liquid fuel in the form of ethanol in the next stage. Hydrolysis is carried out using sulfuric acid. The results showed that from as much as 10 grams of dried corn cobs were crushed then oven for 4 hours at a temperature of 60oC then added 100 mL of sulfuric acid solution in various normalities. Hydrolysis is run at a temperature of 100 Oc, the results of hydrolysis are analyzed at various time variations. The results of the trial showed hydrolysis using sulfuric acid with a variation of time can convert corncob into glucose ± 54 mL.